ANALISIS MANFAAT UPAYA PENANGKAPAN IKAN KARANG DI DESA WAWATU KECAMATAN MORAMO UTARA KABUPATEN KONAWE SELATAN - Ari Sandy Muchtar; Baru Sadarun; Roslindah Daeng Siang (Jurnal Bisnis Perikanan (Journal of Fishery Business), 2014)
The research goals is to analyze the value of the advantages of each type of fishing gear and assess the benefits of reef fish resources through fishing effort in the village Wawatu. The research was conducted using survey method, i.e. direct observation and interviews. The sample in this study was determined by census technique and all members of the population used as samples. Based on the survey results revealed that reef fishing effort carried out by using fishing gear fishing, bottom trawling (gill net), and a combination of fishing and bottom trawling. Each obtained value of the benefit or advantage that Rp3.694.937, Rp3.520.390, and 3,202,165 respectively. And the value of direct benefits reef fishing effort is Rp4.273.000 pertrip. Where fishermen doing fishing effort as much as 29 times per month, meaning the value of the benefits of reef fishing at Rp67.010.850 per month or Rp804.130.200 /year/ 25.24 ha, or Rp31.859.359 /year/ha. The low value of the reef fish resources direct benefits in the Wawatu village is due to the less optimal utilization by the society. It is needed the socialize benefits of resources in order to get more optimal utilization and to improve the welfare of society